A high wear resistant modified nylon-based material and a method of making the same
Patent Information
- Application Number
- CN202510738331.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-04
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-06-04
AI Technical Summary
[0003]然而,传统尼龙基体的摩擦学性能尚不足以应对高频次机械运动的需求
1、本发明技术方案中,通过分阶段化学改性构建的“交联-氟化”协同结构,赋予材料卓越的耐磨性能。首先,在尼龙6预聚物中引入二乙烯苯共价交联网络,形成三维分子骨架,有效限制分子链的滑移与塑性变形,抵抗摩擦剪切力的破坏。其次,全氟丁基乙烯接枝形成的氟化表面层显著降低材料表面能,减少摩擦副间的粘着效应,同时氟化碳碎片在摩擦界面形成自润滑转移膜,进一步降低摩擦系数。此外,氮化硼的层状结构与二氧化硅的硬质颗粒协同机制,分别降低剪切应力与提高表面硬度,使材料在高频动态载荷下仍能维持稳定的摩擦学性能,大幅延长使用寿命。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of polyamide materials technology, and in particular to a high wear-resistant modified nylon-based material and its preparation method. Background Technology
[0002] Since its industrial application in the mid-20th century, nylon (PA) has become one of the five most widely used engineering plastics. In the field of machinery manufacturing, nylon materials, with their high specific strength, self-lubricating properties, and good fatigue resistance, are widely used in the manufacture of key moving parts such as gears, bearings, and guide rails. Especially with the rapid development of Industry 4.0 and intelligent manufacturing, robotics technology has placed higher demands on the comprehensive performance of structural materials: they need to withstand high-frequency dynamic loads while maintaining stable tribological properties under limited lubrication conditions, posing new technical challenges to traditional nylon materials. In robot systems, the service environment of core components such as joint components, transmission mechanisms, and load-bearing frames is particularly harsh. Taking a six-axis industrial robot as an example, its rotary joints need to complete hundreds of precision movements per minute, and the transmission components are subjected to large contact stresses for extended periods, accompanied by high relative sliding speeds.
[0003] However, the tribological properties of traditional nylon matrices are insufficient to meet the demands of high-frequency mechanical motion. A high coefficient of friction not only exacerbates energy loss during motion but also easily triggers localized temperature rises, while the material's inherent thermal stability leads to a gradual decline in mechanical properties. Furthermore, under continuous contact stress, the material's wear rate still falls short of the long-term service requirements of precision transmission components. Accumulated surface damage can cause problems such as widened clearances and decreased motion accuracy, and in severe cases, even mechanical jamming or functional failure. Summary of the Invention
[0004] To address the problems mentioned in the background section, this invention provides a highly wear-resistant modified nylon-based material and its preparation method.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: A highly wear-resistant modified nylon-based material comprises the following raw materials by weight: 50-70 parts modified nylon, 5-8 parts glass fiber, 1-3 parts silane coupling agent, 1-3 parts boron nitride, 2-5 parts silicon dioxide, and 0.2-0.6 parts heat stabilizer.
[0006] Furthermore, the silane coupling agent includes one of the following: silane coupling agent KH-550, silane coupling agent KH-792, silane coupling agent KH-560, and silane coupling agent KH-570.
[0007] Furthermore, the heat stabilizer includes one of triphenyl phosphite, tri(nonylphenyl) phosphite, calcium stearate, and zinc stearate.
[0008] Furthermore, the modified nylon is prepared by the following steps: S1. Add caprolactam and sodium hydroxide to the reaction vessel, seal and react for 4-5 hours under nitrogen protection. After the reaction is completed, pour the hot reaction solution into methanol, let stand for 1-2 hours, filter the precipitate, wash with methanol 3 times, and dry at 80℃ for 12 hours to obtain nylon 6 prepolymer. S2. Nylon 6 prepolymer was added to N,N-dimethylformamide, followed by divinylbenzene and azobisisobutyronitrile. The mixture was heated and reacted for 4-6 hours under nitrogen protection. After the reaction was completed, the reaction solution was poured into methanol while hot to precipitate the precipitate. After standing for 1-2 hours, the mixture was filtered, washed three times with methanol, and dried at 80°C for 6 hours to obtain mildly crosslinked nylon 6. S3. Add mildly cross-linked nylon 6 to hexafluoroisopropanol, then add perfluorobutylethylene, azobisisobutyronitrile and dodecyl mercaptan. Under nitrogen protection, heat the mixture and react for 10-12 hours. After the reaction is complete, cool the reaction solution to room temperature and add it dropwise to methanol to precipitate the nylon. Let it stand for 10-12 hours, filter it, wash it three times with methanol, and dry it at 60°C for 12 hours to obtain modified nylon.
[0009] Furthermore, in step S1, the mass ratio of caprolactam to sodium hydroxide is 100:(0.3-0.8), and the reaction conditions are: a heating temperature of 240-250℃, a pressure of 0.2-0.4MPa, and a stirring speed of 200-300rpm.
[0010] Further, in step S2, the mass ratio of nylon 6 prepolymer, N,N-dimethylformamide, divinylbenzene and azobisisobutyronitrile is 100:(380-400):(11-13):(0.8-1), and the reaction conditions are: the temperature is 80-85℃ and the stirring speed is 100-200rpm.
[0011] Furthermore, in step S3, the mass ratio of mildly cross-linked nylon 6, hexafluoroisopropanol, perfluorobutylethylene, azobisisobutyronitrile, and dodecanethiol is 100:(400-450):(10-20):(1.5-3):(0.1-0.3), and the reaction conditions are: a heating temperature of 70-75℃ and a stirring speed of 150-250 rpm.
[0012] According to another aspect of the present invention, a method for preparing the above-mentioned high wear-resistant modified nylon-based material is provided, comprising the following steps: Add glass fiber and heat stabilizer to a mixer according to the weight proportions, heat and premix for 5-10 minutes, add silane coupling agent, continue mixing for 10-20 minutes, add modified nylon, boron nitride and silicon dioxide, mix for 15-25 minutes until uniform, add the mixture to a twin-screw extruder, set the temperature range, melt extrude and water-cool and pelletize to obtain a high wear-resistant modified nylon-based material.
[0013] Furthermore, the temperature in the mixer is 80-85℃, and the mixing speed in the mixer is 1000-2000 rpm.
[0014] Furthermore, the granulation temperature in the twin-screw extruder is 240-250℃, and the screw speed is 100-200rpm.
[0015] The beneficial effects of this invention are: 1. In the technical solution of this invention, a "crosslinking-fluorination" synergistic structure constructed through staged chemical modification endows the material with excellent wear resistance. First, a divinylbenzene covalent crosslinking network is introduced into the nylon 6 prepolymer to form a three-dimensional molecular skeleton, effectively restricting the slippage and plastic deformation of molecular chains and resisting the damage caused by frictional shear forces. Second, the fluorinated surface layer formed by perfluorobutylethylene grafting significantly reduces the surface energy of the material and reduces the adhesion effect between friction pairs. At the same time, fluorinated carbon fragments form a self-lubricating transfer film at the friction interface, further reducing the coefficient of friction. In addition, the layered structure of boron nitride and the synergistic mechanism of hard particles of silica reduce shear stress and increase surface hardness, respectively, enabling the material to maintain stable tribological properties under high-frequency dynamic loads and significantly extend its service life.
[0016] 2. In the technical solution of this invention, the cross-linked network inhibits the high-temperature relaxation of molecular chains and slows down the thermal decomposition process through the thermal binding effect of covalent bonds. The chemical inertness of the surface fluorinated layer forms a dense barrier, blocking the penetration of oxygen, moisture and corrosive media, and reducing the risk of hydrolysis and oxidation of the nylon backbone. The composite heat stabilizer, through a dual mechanism of chelating metal ions and capturing free radicals, synergistically blocks the thermal oxidation chain reaction, enabling the material to maintain stable mechanical properties under high-temperature conditions, avoiding the performance degradation caused by thermal softening of traditional nylon.
[0017] 3. In the technical solution of this invention, after the glass fiber is surface-modified with a silane coupling agent, it forms a strong interfacial bond with the nylon matrix, improving tensile strength and impact resistance through fiber bridging effect. The cross-linked network imparts rigidity to the material, while the amorphous regions induced by fluorinated side chains allow for local deformation energy dissipation, avoiding brittle fracture caused by excessive cross-linking. Simultaneously, the cross-linked structure and the hydrophobic properties of the fluorinated layer synergistically suppress the nylon's moisture absorption tendency, maintaining dimensional stability and making it suitable for long-term service in precision transmission components.
[0018] 4. In the technical solution of this invention, the low polarity of the surface fluorinated layer and the high chemical stability of the CF bonds give the material significant resistance to oil, acids, alkalis, and organic solvents. The synergistic effect of the cross-linked network and the rigid filler limits swelling and deformation, reducing the media penetration path.
[0019] 5. In the technical solution of this invention, the high-temperature shearing action of the twin-screw extrusion process achieves the orientation of glass fibers and the uniform dispersion of fillers, avoiding interface defects. The activation treatment of the silane coupling agent in the premixing stage strengthens the fiber-matrix interface transition layer, while the fluorinated segments migrate on the surface during the melting process to form a directional lubricating layer, giving the material good melt flowability, stable molding shrinkage, and uniform performance, meeting the needs of industrial production. Detailed Implementation
[0020] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Unless otherwise specified, the raw materials used in this invention are all from commercially available conventional products.
[0022] Preparation Example 1 Modified nylon is prepared by the following steps: S1. Add 100g caprolactam and 0.3g sodium hydroxide to a reaction vessel. Under nitrogen protection, seal the vessel and heat it to 240℃. The pressure is 0.2MPa. Stir the mixture at 200rpm for 4h. After the reaction is complete, pour the hot reaction solution into methanol and let it stand for 1h. Filter the precipitate, wash it three times with methanol, and dry it at 80℃ for 12h to obtain nylon 6 prepolymer. S2. Add 100g of nylon 6 prepolymer to 380g of N,N-dimethylformamide, add 11g of divinylbenzene and 0.8g of azobisisobutyronitrile, heat to 80℃ under nitrogen protection, stir at 100rpm for 4h. After the reaction is completed, pour the reaction solution into methanol while hot to precipitate, let stand for 1h, filter, wash 3 times with methanol, and dry at 80℃ for 6h to obtain mildly crosslinked nylon 6. S3. Add 100g of mildly crosslinked nylon 6 to 400g of hexafluoroisopropanol, add 10g of perfluorobutylethylene, 1.5g of azobisisobutyronitrile and 0.1g of dodecanethiol. Under nitrogen protection, heat to 70℃ and stir at 150rpm for 10h. After the reaction is complete, cool the reaction solution to room temperature, add methanol dropwise to precipitate, let stand for 10h, filter, wash 3 times with methanol, and dry at 60℃ for 12h to obtain modified nylon.
[0023] Preparation Example 2 Modified nylon is prepared by the following steps: S1. Add 100g caprolactam and 0.5g sodium hydroxide to a reaction vessel. Under nitrogen protection, seal the vessel and heat it to 245℃. The pressure is 0.3MPa. Stir the mixture at 250rpm for 4-5 hours. After the reaction is complete, pour the hot reaction solution into methanol and let it stand for 1.5 hours. Filter the precipitate, wash it three times with methanol, and dry it at 80℃ for 12 hours to obtain nylon 6 prepolymer. S2. Add 100g of nylon 6 prepolymer to 391g of N,N-dimethylformamide, add 12.3g of divinylbenzene and 0.9g of azobisisobutyronitrile, and under nitrogen protection, heat to 82℃ and stir at 150rpm for 5h. After the reaction is complete, pour the reaction solution into methanol while hot to precipitate, let stand for 1.5h, filter, wash 3 times with methanol, and dry at 80℃ for 6h to obtain mildly crosslinked nylon 6. S3. Add 100g of mildly crosslinked nylon 6 to 437g of hexafluoroisopropanol, then add 13g of perfluorobutylethylene, 2.2g of azobisisobutyronitrile and 0.2g of dodecanethiol. Under nitrogen protection, heat to 72℃ and stir at 200rpm for 11h. After the reaction is complete, cool the reaction solution to room temperature and precipitate it dropwise into methanol. Let it stand for 11h, filter, wash three times with methanol, and dry at 60℃ for 12h to obtain modified nylon.
[0024] Preparation Example 3 Modified nylon is prepared by the following steps: S1. Add 100g caprolactam and 0.8g sodium hydroxide to a reaction vessel. Under nitrogen protection, seal the vessel and heat it to 250℃. The pressure is 0.4MPa. Stir the mixture at 300rpm for 5h. After the reaction is complete, pour the hot reaction solution into methanol and let it stand for 2h. Filter the precipitate, wash it three times with methanol, and dry it at 80℃ for 12h to obtain nylon 6 prepolymer. S2. Add 100g of nylon 6 prepolymer to 400g of N,N-dimethylformamide, add 13g of divinylbenzene and 1g of azobisisobutyronitrile, and under nitrogen protection, heat to 85℃ and stir at 200rpm for 6h. After the reaction is completed, pour the reaction solution into methanol while hot to precipitate, let stand for 2h, filter, wash 3 times with methanol, and dry at 80℃ for 6h to obtain mildly crosslinked nylon 6. S3. Add 100g of mildly crosslinked nylon 6 to 450g of hexafluoroisopropanol, then add 20g of perfluorobutylethylene, 3g of azobisisobutyronitrile and 0.3g of dodecanethiol. Under nitrogen protection, heat to 75℃ and stir at 250rpm for 12h. After the reaction is complete, cool the reaction solution to room temperature and precipitate it dropwise into methanol. Let it stand for 12h, filter, wash with methanol 3 times, and dry at 60℃ for 12h to obtain modified nylon.
[0025] Example 1 A method for preparing highly wear-resistant modified nylon-based materials includes the following steps: Five parts by weight of glass fiber and 0.2 parts by weight of triphenyl phosphite were added to a mixer, heated to 80°C, and premixed at 1000 rpm for 5 min. One part of silane coupling agent KH-550 was added, and the mixture was continued to be mixed at 1000-2000 rpm for 10 min. Then, 50 parts of the modified nylon prepared in Preparation Example 1, one part of boron nitride, and two parts of silica were added, and the mixture was mixed at 1000 rpm for 15 min until homogeneous. The mixture was then fed into a twin-screw extruder, granulated at 240°C and with a screw speed of 100 rpm. After melt extrusion, the mixture was water-cooled and pelletized to obtain a high-wear-resistant modified nylon-based material.
[0026] Example 2 A method for preparing highly wear-resistant modified nylon-based materials includes the following steps: Six parts by weight of glass fiber and 0.4 parts by weight of tri(nonylphenyl) phosphite were added to a mixer, heated to 82°C, and premixed at 1500 rpm for 8 min. Two parts by weight of silane coupling agent KH-792 were added, and mixing was continued at 1500 rpm for 15 min. Sixty-one parts of the modified nylon prepared in Preparation Example 2, two parts by weight of boron nitride, and three parts by weight of silica were added, and mixing was continued at 1500 rpm for 20 min until homogeneous. The mixture was then fed into a twin-screw extruder, granulated at 245°C and with a screw speed of 150 rpm. After melt extrusion, the mixture was water-cooled and pelletized to obtain a high-wear-resistant modified nylon-based material.
[0027] Example 3 A method for preparing highly wear-resistant modified nylon-based materials includes the following steps: Eight parts by weight of glass fiber and 0.6 parts by weight of calcium stearate were added to a mixer, heated to 85°C, and premixed at 2000 rpm for 10 min. Three parts by weight of silane coupling agent KH-570 were added, and mixing was continued at 2000 rpm for 20 min. Seventy parts by weight of the modified nylon prepared in Preparation Example 3, three parts by weight of boron nitride, and two to five parts by weight of silica were added, and mixing was continued at 2000 rpm for 25 min until homogeneous. The mixture was then fed into a twin-screw extruder, granulated at 250°C and with a screw speed of 200 rpm. After melt extrusion, the mixture was water-cooled and pelletized to obtain a high-wear-resistant modified nylon-based material.
[0028] Comparative Example 1 The difference between this comparative example and Preparation Example 1 is that divinylbenzene is not added in step S2, while the remaining steps are the same as in Preparation Example 1, resulting in nylon material.
[0029] Comparative Example 2 The difference between this comparative example and preparation example 2 is that perfluorobutylethylene is not added in step S3, while the remaining steps are the same as in preparation example 2, resulting in nylon material.
[0030] Comparative Example 3 The difference between this comparative example and Example 1 is that the nylon material obtained in Comparative Example 1 is used instead of the modified nylon obtained in Preparation Example 1, while the remaining steps are the same as in Example 1.
[0031] Comparative Example 4 The difference between this comparative example and Example 2 is that the nylon material obtained in Comparative Example 2 is used instead of the modified nylon obtained in Preparation Example 2, while the remaining steps are the same as in Example 2.
[0032] Comparative Example 5 The difference between this comparative example and Example 3 is that commercially available nylon 6 was used instead of the modified nylon prepared in Example 3, while the remaining steps were the same as in Example 3.
[0033] Referring to ASTM G99, "Test Method for Wear Testing Using a Needle Plate Tester," the nylon-based materials from Examples 1-3 and Comparative Examples 3-5 were injection molded into standard block specimens with dimensions of 30mm × 7mm × 6mm and a 30mm × 7mm flat contact surface. The specimen surfaces were polished with 2000-grit sandpaper. All specimens were placed in a 50°C drying oven for 24 hours before testing. A GCr15 steel ring was fixed to the spindle of the testing machine, and the specimen was vertically mounted in the fixture, ensuring the contact surface was parallel to the steel ring axis. The testing machine was started, loaded to 200N, and pre-run for 5 minutes at a speed of 200rpm to eliminate surface micro-protrusions. The machine was then run continuously for 2 hours for the formal test, and the torque (T, in N·m) was recorded. This was repeated three times. After the test, the specimens were unloaded and removed. The coefficient of friction (μ) was calculated: μ = T / (F·r), where T is the torque, F is the load, and r is the steel ring radius of 20 mm. The results are shown in Table 1. Table 1. Test results of tribological properties of Examples 1-3 and Comparative Examples 3-5
[0034] The nylon-based materials of Examples 1-3 and Comparative Examples 3-5 were cut into I-shaped dumbbell specimens with dimensions of 57mm×13mm×3mm and a total length of 165mm. The surface of the specimens was polished with 2000-grit sandpaper to obtain tensile specimens.
[0035] The nylon-based materials of Examples 1-3 and Comparative Examples 3-5 were processed into rectangular specimens with dimensions of 63.5 mm × 12.7 mm × 3.2 mm. A notch was made in the middle of the specimen with a notch depth of 2.5 mm and a root radius of 0.25 mm to obtain notched impact specimens.
[0036] All samples were placed in a constant temperature and humidity chamber at 23±2℃ and 50±5% for 48 hours. Before the test, the sample surface was wiped with anhydrous ethanol to remove dust and grease.
[0037] (I) Tensile property test: The specimen is vertically mounted in the fixture of the universal testing machine, ensuring that the gauge length is aligned with the tensile axis. The tensile rate is set to 50 mm / min. After the specimen breaks, the test is stopped immediately, and the length of the gauge length at the point of breakage (L) is recorded. 断裂 ) and maximum load (F max Repeat this process three times to calculate the tensile strength (σ) and elongation at break (ε). The calculation formulas are as follows:
[0038]
[0039] Where A0 is the initial cross-sectional area and L0 is the initial gauge length.
[0040] (II) Notched Impact Strength Test: Use a pendulum impact testing machine (range 0-25J, accuracy ±1%) to calibrate the pendulum energy and impact velocity (3.5m / s). Adjust the specimen support span to 40mm, ensuring the notch faces away from the impact direction. Place the notched specimen horizontally on the support platform, with the notch center aligned with the pendulum cutting edge. Release the pendulum, impact the specimen, and record the impact energy (E). Repeat 3 times. Calculate the notched impact strength (a). k The calculation formula is as follows:
[0041] Where b is the sample width and d is the sample thickness.
[0042] The results of the tensile property test and the notched impact strength test are shown in Table 2: Table 2. Mechanical property test results of Examples 1-3 and Comparative Examples 3-5
[0043] As shown in Table 1, the coefficients of friction of Examples 1-3 are significantly lower than those of Comparative Examples 3-5. The coefficients of friction for Examples 1-3 range from 0.09 to 0.11, while those for Comparative Examples 3-5 range from 0.18 to 0.36. The torque of Examples 1-3 is also significantly lower than that of Comparative Examples 3-5, with torques ranging from 0.36 to 0.43 N·m for Examples 1-3 and from 0.70 to 1.42 N·m for Comparative Examples 3-5. This indicates that the high-wear-resistant modified nylon-based materials prepared in Examples 1-3 possess better wear resistance.
[0044] As shown in Table 2, the tensile strength, elongation at break, and notched impact strength of Examples 1-3 are all superior to those of Comparative Examples 3-5. The tensile strength of Examples 1-3 is 97-106 MPa, while that of Comparative Examples 3-5 is 53-76 MPa. The elongation at break of Examples 1-3 is 13.0-15.5%, while that of Comparative Examples 3-5 is 19.5-32.0%. Although the elongation at break of the comparative examples seems higher, in practical applications, materials need sufficient strength while maintaining a certain level of toughness. Furthermore, the low tensile strength of the comparative examples indicates poor overall mechanical properties. The notched impact strength of Examples 1-3 is 10.8-13.4 kJ / m², while that of Comparative Examples 3-5 is 4.8-8.2 kJ / m². This indicates that the materials of Examples 1-3 have better mechanical properties.
[0045] In step S2 of Preparation Examples 1-3, divinylbenzene was added to form a slightly cross-linked structure in nylon 6, which restricted the movement of nylon molecular chains, enhanced the interaction forces between molecular chains, and reduced slippage and detachment of molecular chains during friction, thereby reducing the coefficient of friction and torque and improving wear resistance. In contrast, Comparative Example 1 did not add divinylbenzene in step S2, and the nylon 6 did not form a cross-linked structure. The molecular chains moved relatively freely and were prone to slippage and detachment during friction, potentially leading to an increase in the coefficient of friction and torque and a decrease in wear resistance. Comparative Example 3, in which the nylon material prepared in Comparative Example 1 was used instead of the modified nylon prepared in Preparation Example 1, showed a significant deterioration in its tribological properties.
[0046] In step S3 of Preparation Examples 1-3, perfluorobutylethylene was added, introducing fluorinated groups onto the nylon molecular chain. These fluorinated groups have low surface energy, enabling the formation of a low-friction interface layer on the material surface, reducing adhesion to the mating materials and lowering the friction coefficient. Simultaneously, the fluorinated groups also improve the hydrophobicity and chemical stability of the material, reducing wear caused by the erosion of the material by moisture and chemicals. In Comparative Example 2, no perfluorobutylethylene was added in step S3; therefore, the nylon material surface did not form a low-friction interface layer, resulting in a relatively high friction coefficient. Comparative Example 4, which used the nylon material obtained in Comparative Example 2 instead of the modified nylon obtained in Preparation Example 2, also showed a decrease in its tribological properties.
[0047] The slightly cross-linked structure enhances the interaction forces between nylon molecular chains, enabling the material to better transfer stress under load and improving its tensile strength and notched impact strength. Comparative Example 1, lacking a cross-linked structure, has weaker interaction forces between molecular chains, making it prone to slippage and breakage under load, resulting in lower tensile strength and notched impact strength. Comparative Example 3, where the nylon material obtained from Comparative Example 1 was used instead of the modified nylon obtained in Preparation Example 1, exhibited significantly worse mechanical properties.
[0048] The introduction of fluorine-containing groups improves the interfacial properties of the material to some extent, making the bond between fillers such as glass fiber, boron nitride, and silica and the nylon matrix tighter, thus improving the overall mechanical properties of the material. Comparative Example 2, lacking fluorine-containing groups, has a relatively weaker bond between the filler and the nylon matrix, affecting the material's mechanical properties. Comparative Example 4, which uses the nylon material prepared in Comparative Example 2 instead of the modified nylon prepared in Preparation Example 2, also shows a decrease in mechanical properties. Comparative Example 5 uses commercially available nylon 6, which has not undergone modification treatment; its molecular chain structure and properties differ significantly from the modified nylon, resulting in the worst mechanical properties.
[0049] In summary, by introducing a slightly cross-linked structure and fluorine-containing groups during the nylon preparation process, the prepared modified nylon significantly improves the tribological and mechanical properties of the high wear-resistant modified nylon-based material.
[0050] In the description of this specification, the terms "preparation example," "example," "various examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that example or preparation example, which are included in at least one example or preparation example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same example or preparation example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more examples or preparation examples.
[0051] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A highly wear-resistant modified nylon-based material, characterized in that, The raw materials include, by weight, 50-70 parts modified nylon, 5-8 parts glass fiber, 1-3 parts silane coupling agent, 1-3 parts boron nitride, 2-5 parts silica, and 0.2-0.6 parts heat stabilizer; The modified nylon is prepared by the following steps: S1. Add caprolactam and sodium hydroxide to the reaction vessel, seal and react for 4-5 hours under nitrogen protection. After the reaction is completed, pour the reaction solution into methanol while it is hot, let it stand for 1-2 hours, filter the precipitate, wash and dry it to obtain nylon 6 prepolymer. S2. Add nylon 6 prepolymer to N,N-dimethylformamide, add divinylbenzene and azobisisobutyronitrile, and react under nitrogen protection for 4-6 hours. After the reaction is completed, pour the reaction solution into methanol while hot to precipitate. After standing for 1-2 hours, filter, wash and dry to obtain mildly cross-linked nylon 6. S3. Add mildly cross-linked nylon 6 to hexafluoroisopropanol, add perfluorobutylethylene, azobisisobutyronitrile and dodecyl mercaptan, and heat the reaction for 10-12 hours under nitrogen protection. After the reaction is completed, cool the reaction solution to room temperature, add methanol dropwise to precipitate, let stand for 10-12 hours, filter, wash and dry to obtain modified nylon. In step S2, the mass ratio of nylon 6 prepolymer, N,N-dimethylformamide, divinylbenzene and azobisisobutyronitrile is 100:(380-400):(11-13):(0.8-1), and the reaction conditions are: the temperature is 80-85℃ and the stirring speed is 100-200rpm. In step S3, the mass ratio of mildly cross-linked nylon 6, hexafluoroisopropanol, perfluorobutylethylene, azobisisobutyronitrile, and dodecanethiol is 100:(400-450):(10-20):(1.5-3):(0.1-0.3), and the reaction conditions are: the temperature is 70-75℃ and the stirring speed is 150-250 rpm.
2. The high wear-resistant modified nylon-based material according to claim 1, characterized in that, Silane coupling agents include one of silane coupling agents KH-550, KH-792, KH-560, and KH-570.
3. The high wear-resistant modified nylon-based material according to claim 1, characterized in that, Heat stabilizers include one of triphenyl phosphite, tri(nonylphenyl) phosphite, calcium stearate, and zinc stearate.
4. The high wear-resistant modified nylon-based material according to claim 1, characterized in that, In step S1, the mass ratio of caprolactam to sodium hydroxide is 100:(0.3-0.8), and the reaction conditions are: a temperature of 240-250℃, a pressure of 0.2-0.4MPa, and a stirring speed of 200-300rpm.
5. A method for preparing a high-wear-resistant modified nylon-based material as described in any one of claims 1-4, characterized in that, Includes the following steps: Add glass fiber and heat stabilizer to a mixer according to the weight proportions, heat and premix for 5-10 minutes, add silane coupling agent, continue mixing for 10-20 minutes, add modified nylon, boron nitride and silicon dioxide, mix for 15-25 minutes until uniform, add the mixture to a twin-screw extruder, set the temperature range, melt extrude and water-cool and pelletize to obtain a high wear-resistant modified nylon-based material.
6. The method for preparing the high wear-resistant modified nylon-based material according to claim 5, characterized in that, The temperature in the mixer is 80-85℃, and the mixing speed in the mixer is 1000-2000 rpm.
7. The method for preparing the high wear-resistant modified nylon-based material according to claim 5, characterized in that, The granulation temperature in the twin-screw extruder is 240-250℃, and the screw speed is 100-200rpm.
Citation Information
Patent Citations
Multi-component compound modified nylon 6 composite material for carrier roller and preparation method thereof
CN103467978A
High-strength screen cloth and preparation method thereof
CN119392396A
Terpolymers of tetrafluoroethylene, ethylene and perfluoroalkyl vinyl monomer and process for producing the same
US4123602A